Composite oxide, catalyst for methanol production, and method for producing composite oxide

By using composite oxides composed of Cu, Zn and Zr, the problem of poor catalytic performance of existing catalysts is solved, and a more efficient carbon dioxide methanolation reaction is achieved, and the catalytic performance is improved.

CN119585043APending Publication Date: 2025-03-07MITSUI MINING & SMELTING CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380055445.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-04
Filing Date
2023-08-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The catalytic performance of existing carbon dioxide methanolation catalysts is insufficient, and it is difficult to effectively promote the reaction between carbon dioxide and hydrogen.

Method used

Using a composite oxide including Cu, Zn and Zr, a composite oxide having a specific surface area of ​​50 m2/g or more and a Cu dispersion of 6.5% was prepared by a specific production method and process, and applied to methanol production.

Benefits of technology

The catalytic performance of carbon dioxide methanolation is significantly improved, the CO2 conversion rate and methanol yield are improved, and more efficient methanol synthesis is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005252159360000221
    Figure BDA0005252159360000221
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a composite oxide having improved carbon dioxide methanation catalytic performance; a catalyst for methanol production comprising the composite oxide; and a method for producing a composite oxide suitable for the production of the composite oxide. The present invention provides: a composite oxide which contains Cu, Zn and Zr, has a specific surface area of 50 m2 / g or more, and has a Cu dispersion degree of 6.5% or more; a catalyst for methanol production, which contains the composite oxide; and a method for producing a composite oxide, which is suitable for the production of the composite oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite oxide, a catalyst for producing methanol, and a method for producing the composite oxide. Background Art

[0002] In recent years, efforts to reduce greenhouse gas emissions such as carbon dioxide have continued to increase worldwide. As one of the measures to reduce carbon dioxide, catalysts that promote the methanolization reaction of carbon dioxide (CO2+3H2→CH3OH+H2O) have attracted attention, and various carbon dioxide methanolization catalysts have been developed.

[0003] For example, Patent Document 1 describes a carbon dioxide methanolization catalyst comprising copper oxide, zinc oxide, and zirconium oxide, and further comprising at least one element selected from the group consisting of aluminum, chromium, and palladium.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 7-39755 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] However, the carbon dioxide methanolization catalyst described in Patent Document 1 does not have sufficient catalytic performance for carbon dioxide methanolization.

[0009] Therefore, an object of the present invention is to provide a composite oxide having improved catalytic performance for methanolization of carbon dioxide, a catalyst for methanol production containing the composite oxide, and a method for producing the composite oxide suitable for producing the composite oxide.

[0010] Solutions for solving problems

[0011] The present invention provides the following composite oxide, catalyst for methanol production, method for producing the composite oxide, and method for producing methanol.

[0012] [1] A composite oxide comprising Cu, Zn and Zr, having a specific surface area of ​​50 m 2 / g or more, and the Cu dispersion is 6.5% or more.

[0013] [2] A composite oxide according to [1], wherein the contents of Cu, Zn and Zr in the composite oxide are respectively 40 mol% to 90 mol%, 5 mol% to 40 mol%, and 1 mol% to 15 mol%, based on the total content of all metal elements in the composite oxide.

[0014] [3] The composite oxide according to [1] or [2], further comprising one or two metal elements selected from Mg and Al.

[0015] [4] The composite oxide according to any one of [1] to [3], wherein the CuO crystallite diameter is 2.0 nm or more and 25.0 nm or less.

[0016] [5] A catalyst for methanol production, comprising the composite oxide according to any one of [1] to [4].

[0017] [6] A method for producing a composite oxide, comprising the following steps:

[0018] Step (a), adding an acidic aqueous solution containing two or more metal ions to an alkaline aqueous solution having a pH of 7.5 or more and 11 or less to form a precipitate containing two or more metal elements; and

[0019] In step (b), the precipitate is calcined to produce a composite oxide containing the two or more metal elements.

[0020] [7] The production method according to [6], wherein in step (a), the pH of the alkaline aqueous solution after the addition of the acidic aqueous solution is 5 to 9.

[0021] [8] The production method according to [6] or [7], wherein the acidic aqueous solution used in step (a) contains Cu ions, Zn ions and Zr ions, and the composite oxide produced in step (b) contains Cu, Zn and Zr.

[0022] [9] The production method according to any one of [6] to [8], wherein the composite oxide produced in step (b) further contains one or two metal elements selected from Mg and Al.

[0023]

[10] The production method according to any one of [6] to [9], wherein the composite oxide produced in step (b) is the composite oxide according to any one of [1] to [4].

[0024]

[11] A method for producing methanol, comprising the step of contacting CO2 gas and H2 gas under conditions of 100°C to 400°C and 0.1 MPa to 30 MPa in the presence of a composite oxide according to any one of [1] to [4] that has been subjected to a reduction treatment.

[0025] Effects of the Invention

[0026] According to the present invention, there are provided a composite oxide having improved catalytic performance for methanolization of carbon dioxide, a catalyst for methanol production containing the composite oxide, and a method for producing the composite oxide suitable for producing the composite oxide. DETAILED DESCRIPTION

[0027] 《Compound Oxide》

[0028] The composite oxide of the present invention is described below. It should be noted that "composite oxide" refers to an oxide containing two or more metal elements. "Composite oxide" includes, for example, a composite of two or more metal oxides and a solid solution of two or more metal oxides.

[0029] <Morphology of composite oxide>

[0030] The composite oxide of the present invention is in the form of a powder, for example. The composite oxide of the present invention may be formed into a desired form such as a pellet or a layer.

[0031] <Physical properties of composite oxides>

[0032] The composite oxide of the present invention preferably has one or more of the specific surface area, Cu dispersion and CuO crystallite diameter described below; more preferably has the specific surface area and Cu dispersion described below; further preferably has the specific surface area, Cu dispersion and CuO crystallite diameter described below.

[0033] From the viewpoint of improving the diffusibility of the raw gas (CO2 and H2) for methanol production in the composite oxide of the present invention and improving the catalytic performance of carbon dioxide methanolization of the composite oxide of the present invention (e.g., CO2 conversion rate, methanol yield, etc.), the specific surface area of ​​the composite oxide of the present invention is preferably 50 m 2 / g or more, more preferably 90m 2 / g or more, more preferably 95m 2 / g or more. The upper limit is not particularly limited. The specific surface area of ​​the composite oxide of the present invention can be, for example, 130 m 2 / g or less, can also be 125m 2 / g or less, and can also be 120m 2 These upper limits may be combined with any of the above lower limits. The specific surface area may be measured, for example, by the method described in the Examples.

[0034] From the viewpoint of improving the contact between Cu in the composite oxide of the present invention and the raw material gas (CO2 and H2) for methanol production and improving the carbon dioxide methanolization catalytic performance of the composite oxide of the present invention (e.g., CO2 conversion rate, methanol yield, etc.), the Cu dispersion of the composite oxide of the present invention is preferably 6.5% or more, more preferably 7.0% or more, and further preferably 8.0% or more. The upper limit is not particularly limited. The Cu dispersion of the composite oxide of the present invention can be, for example, less than 30%, less than 20%, or less than 15%. These upper limits can be combined with any of the above-mentioned lower limits, respectively. The determination of Cu dispersion can be carried out, for example, according to the method described in the examples.

[0035] The CuO crystallite diameter in the composite oxide of the present invention contributes to the Cu dispersion of the composite oxide of the present invention. From the viewpoint of achieving the above-mentioned Cu dispersion of the composite oxide of the present invention and improving the carbon dioxide methanolization catalytic performance (e.g., CO2 conversion rate, methanol yield, etc.) of the composite oxide of the present invention, the CuO crystallite diameter of the composite oxide of the present invention is preferably 2.0 nm or more and 25.0 nm or less, more preferably 3.0 nm or more and 20.0 nm or less, and further preferably 4.0 nm or more and 10.0 nm or less. The determination of the CuO crystallite diameter can be carried out, for example, according to the method described in the examples.

[0036] <Composition of composite oxide>

[0037] The composite oxide of the present invention contains Cu, Zn and Zr. It should be noted that the composite oxide of the present invention contains O in addition to Cu, Zn and Zr.

[0038] From the viewpoint of achieving one or more of the above-mentioned specific surface area, Cu dispersion and CuO crystallite diameter and improving the catalytic performance of carbon dioxide methanolization of the composite oxide of the present invention (for example, CO2 conversion rate, methanol yield, etc.), based on the total content (total molar amount) of all metal elements in the composite oxide of the present invention, the Cu content (molar amount) in the composite oxide of the present invention is preferably greater than 40 mol % and less than 90 mol %, more preferably greater than 45 mol % and less than 80 mol %, and even more preferably greater than 55 mol % and less than 75 mol %.

[0039] In the composite oxide of the present invention, Cu can form a solid solution phase together with Zn, Zr and O (for example, a solid solution phase of CuO, ZnO and ZrO2, a solid solution phase of CuO and ZnO, a solid solution phase of CuO and ZrO2, etc.), or form a separate phase (CuO phase) belonging to a crystalline phase or an amorphous phase together with O, or form both a solid solution phase and a separate phase.

[0040] From the viewpoint of achieving one or more of the above-mentioned specific surface area, Cu dispersion and CuO crystallite diameter and improving the catalytic performance of carbon dioxide methanolization of the composite oxide of the present invention (for example, CO2 conversion rate, methanol yield, etc.), based on the total content (total molar amount) of all metal elements in the composite oxide of the present invention, the Zn content (molar amount) in the composite oxide of the present invention is preferably greater than 5 mol % and less than 40 mol %, more preferably greater than 10 mol % and less than 35 mol %, and further preferably greater than 20 mol % and less than 30 mol %.

[0041] Cu and Zn play a role as adsorption sites for raw gas (CO2 and H2) for methanol production, and contribute to the stabilization and activation of reaction intermediates. In addition, the interaction between Cu and Zn contributes to Cu dispersity. From the viewpoint of enhancing the interaction between Cu and Zn, the molar ratio of Cu relative to the molar ratio of Zn is preferably 1.0 or more and 5.0 or less, more preferably 2.0 or more and 4.0 or less, and further preferably 2.5 or more and 3.0 or less.

[0042] In the composite oxide of the present invention, Zn can form a solid solution phase together with Cu, Zr and O (for example, a solid solution phase of ZnO, CuO and ZrO2, a solid solution phase of ZnO and CuO, a solid solution phase of ZnO and ZrO2, etc.), or form a separate phase (ZnO phase) belonging to a crystalline phase or an amorphous phase together with O, or form both a solid solution phase and a separate phase.

[0043] From the viewpoint of achieving one or more of the above-mentioned specific surface area, Cu dispersion and CuO crystallite diameter and improving the catalytic performance of the carbon dioxide methanolization of the composite oxide of the present invention (for example, CO2 conversion rate, methanol yield, etc.), based on the total content (total molar amount) of all metal elements in the composite oxide of the present invention, the Zr content (molar amount) in the composite oxide of the present invention is preferably greater than 1 mol % and less than 15 mol %, more preferably greater than 2 mol % and less than 13 mol %, and even more preferably greater than 4 mol % and less than 12 mol %.

[0044] In the composite oxide of the present invention, Zr can form a solid solution phase together with Cu, Zn and O (for example, a solid solution phase of ZrO2, CuO and ZnO, a solid solution phase of ZrO2 and CuO, a solid solution phase of ZrO2 and ZnO, etc.), or form a separate phase (ZrO2 phase) belonging to a crystalline phase or an amorphous phase together with O, or form both a solid solution phase and a separate phase.

[0045] The composite oxide of the present invention may contain one or two or more other metal elements in addition to Cu, Zn and Zr.

[0046] From the viewpoint of achieving one or more of the above-mentioned specific surface area, Cu dispersion and CuO crystallite diameter and improving the carbon dioxide methanolization catalytic performance (such as CO2 conversion rate, methanol yield, etc.) of the composite oxide of the present invention, the other metal elements are preferably one or two metal elements selected from Mg and Al.

[0047] In the case where the composite oxide of the present invention contains one or more other metal elements, from the viewpoint of achieving one or more of the above-mentioned specific surface area, Cu dispersion and CuO crystallite diameter and improving the carbon dioxide methanolization catalytic performance of the composite oxide of the present invention (for example, CO2 conversion rate, methanol yield, etc.), the total content (total molar amount) of Cu, Zn and Zr in the composite oxide of the present invention is preferably 70 mol% or more and 99 mol% or less, more preferably 75 mol% or more and 99 mol% or less, and further preferably 80 mol% or more and 99 mol% or less, based on the total content (total molar amount) of all metal elements in the composite oxide of the present invention.

[0048] In the case where the composite oxide of the present invention contains one or more other metal elements, from the viewpoint of achieving one or more of the above-mentioned specific surface area, Cu dispersion and CuO crystallite diameter and improving the carbon dioxide methanolization catalytic performance of the composite oxide of the present invention (for example, CO2 conversion rate, methanol yield, etc.), the content (molar amount) of one or more other metal elements in the composite oxide of the present invention is preferably 1 mol% or more and 30 mol% or less, more preferably 1 mol% or more and 25 mol% or less, and further preferably 1 mol% or more and 20 mol% or less, based on the total content (total molar amount) of all metal elements in the composite oxide of the present invention. For "the content (molar amount) of one or more other metal elements", when the composite oxide of the present invention contains one other metal element, it refers to the content (molar amount) of the one metal element, and when the composite oxide of the present invention contains two or more other metal elements, it refers to the total content (total molar amount) of the two or more metal elements.

[0049] In the composite oxide of the present invention, other metal elements can form a solid solution phase with Cu, Zn, Zr and O (for example, oxides of other metal elements and solid solution phases of CuO, ZnO and ZrO2, oxides of other metal elements and solid solution phases of CuO and ZnO, oxides of other metal elements and solid solution phases of CuO and ZrO2, oxides of other metal elements and solid solution phases of ZnO and ZrO2, oxides of other metal elements and solid solution phases of CuO, oxides of other metal elements and solid solution phases of ZnO, oxides of other metal elements and solid solution phases of CuO and ZrO2, etc.), or form a single phase (oxide phase of other metal elements) belonging to a crystalline phase or an amorphous phase with O, or form both a solid solution phase and a single phase. The oxide of Mg is MgO, and the oxide of Al is Al2O3.

[0050] In the case where the composite oxide of the present invention contains Mg, from the viewpoint of achieving one or more of the above-mentioned specific surface area, Cu dispersion and CuO crystallite diameter and improving the carbon dioxide methanolization catalytic performance of the composite oxide of the present invention (for example, CO2 conversion rate, methanol yield, etc.), the Mg content (molar amount) in the composite oxide of the present invention is preferably greater than 0.1 mol % and less than 10 mol %, more preferably greater than 0.5 mol % and less than 7 mol %, and further preferably greater than 1 mol % and less than 5 mol %, based on the total content (total molar amount) of all metal elements in the composite oxide of the present invention.

[0051] In the case where the composite oxide of the present invention contains Al, from the viewpoint of achieving one or more of the above-mentioned specific surface area, Cu dispersion and CuO crystallite diameter and improving the carbon dioxide methanolization catalytic performance of the composite oxide of the present invention (for example, CO2 conversion rate, methanol yield, etc.), based on the total content (total molar amount) of all metal elements in the composite oxide of the present invention, the Al content (molar amount) in the composite oxide of the present invention is preferably greater than 0.1 mol % and less than 30 mol %, more preferably greater than 1 mol % and less than 25 mol %, and further preferably greater than 5 mol % and less than 20 mol %.

[0052] The content of each metal element in the composite oxide of the present invention can be measured by a conventional method such as inductively coupled plasma atomic emission spectrometry (ICP-AES or ICP-OES).

[0053] 《Catalysts for methanol production》

[0054] Hereinafter, the catalyst for methanol production of the present invention will be described.

[0055] The catalyst for methanol production of the present invention comprises the composite oxide of the present invention. Therefore, the catalyst for methanol production of the present invention can exhibit excellent carbon dioxide methanolization catalytic performance (for example, CO2 conversion rate, methanol yield, etc.).

[0056] The catalyst for methanol production of the present invention catalyzes the reaction of producing methanol from raw material gases (CO 2 and H 2 ) for methanol production, that is, the methanol synthesis reaction represented by the following formula.

[0057] CO2+3H2→CH3OH+H2O

[0058] Cu and Zn play a role as adsorption sites for raw gas (CO2 and H2) for methanol production, and contribute to the stabilization and activation of reaction intermediates. In addition, the interaction between Cu and Zn contributes to the Cu dispersion. In the catalytic action of the composite oxide of the present invention, the interaction between Cu and Zn is important.

[0059] Zr enhances the interaction between Cu and Zn and functions as an adsorption site for CO 2. Furthermore, the interaction between Cu and Zr contributes to the stabilization of the adsorption sites for the raw material gases (CO 2 and H 2) for methanol production.

[0060] Mg and Al will enhance the interaction between Cu and Zn.

[0061] 《Method for producing methanol》

[0062] Hereinafter, the method for producing methanol of the present invention will be described.

[0063] The method for producing methanol of the present invention includes a step of bringing CO 2 gas and H 2 gas into contact in the presence of the composite oxide of the present invention that has been subjected to a reduction treatment.

[0064] In order to reduce the Cu oxide (i.e., CuO) contained in the composite oxide of the present invention to form Cu whose valence state is lower than that before reduction, the composite oxide of the present invention is subjected to reduction treatment before using the composite oxide of the present invention in a methanol synthesis reaction. The reduction treatment can be carried out, for example, by heat treating the composite oxide of the present invention in a hydrogen atmosphere at a temperature of 100° C. to 300° C. for 0.5 hours to 4 hours. The reduction treatment of the composite oxide of the present invention can be carried out twice or more. Specific examples of the conditions of each reduction treatment are as described above.

[0065] By bringing CO 2 gas and H 2 gas into contact in the presence of the composite oxide of the present invention that has been subjected to a reduction treatment, a methanol synthesis reaction can be carried out, and methanol can be produced. The methanol synthesis reaction is as described above.

[0066] The conditions for the methanol synthesis reaction are not particularly limited as long as the methanol synthesis reaction can be carried out. The temperature is usually 100° C. to 400° C., preferably 150° C. to 350° C., and the pressure is usually 0.1 MPa to 30 MPa, preferably 2 MPa to 20 MPa.

[0067] 《Method for producing composite oxide》

[0068] The manufacturing method of the present invention comprises the following steps:

[0069] Step (a), adding an acidic aqueous solution containing two or more metal ions to an alkaline aqueous solution having a pH of 7.5 or more and 11 or less to form a precipitate containing two or more metal elements; and

[0070] In step (b), the precipitate formed in step (a) is calcined to produce a composite oxide containing two or more metal elements.

[0071] The production method of the present invention is suitable for producing a composite oxide containing Cu, Zn, and Zr, and is particularly suitable for producing the composite oxide of the present invention, but can also be used for producing other composite oxides.

[0072] <Step (a)>

[0073] Step (a) is a step of adding an acidic aqueous solution containing two or more metal ions (hereinafter referred to as "acidic aqueous solution (B)") to an alkaline aqueous solution having a pH of 7.5 or more and 11 or less (hereinafter referred to as "alkaline aqueous solution (A)") to form a precipitate containing two or more metal elements. Hereinafter, the alkaline aqueous solution (A) after the addition of the acidic aqueous solution (B) (i.e., a mixed solution of the alkaline aqueous solution (A) and the acidic aqueous solution (B)) may be referred to as a "reaction solution".

[0074] The alkaline aqueous solution (A) can be prepared, for example, by dissolving a base in water and then adjusting the pH of the resulting aqueous solution as necessary.

[0075] For the alkali used in the preparation of the alkaline aqueous solution (A), as long as it is dissolved in water or reacts with water to generate hydroxide ions, there is no particular restriction, for example, it can be selected from carbonates, bicarbonates, hydroxide salts, ammonium salts, etc., and from the viewpoint of the simplicity of the synthesis operation and the viewpoint of improving the specific surface area of ​​the manufactured composite oxide, it is preferably selected from carbonates and bicarbonates. One alkali can be used alone, or two or more alkalis can be used in combination.

[0076] The carbonate can be selected from alkali metal salts such as sodium carbonate and potassium carbonate; ammonium salts such as ammonium carbonate and ammonium bicarbonate, etc., and is preferably selected from sodium carbonate and potassium carbonate from the viewpoint of simplicity of synthetic operation; sodium carbonate is more preferred. One carbonate may be used alone, or two or more carbonates may be used simultaneously.

[0077] The bicarbonate salt can be selected from alkali metal salts such as sodium bicarbonate and potassium bicarbonate, ammonium bicarbonate, etc., and preferably from alkali metal salts such as sodium bicarbonate and potassium bicarbonate from the viewpoint of reducing the pH change of the reaction solution; sodium bicarbonate is more preferred. One bicarbonate salt can be used alone, or two or more bicarbonates can be used in combination.

[0078] The pH of the alkaline aqueous solution (A) is not particularly limited as long as it is 7.5 or more and 11 or less, but is preferably 7.5 or more and 10 or less, more preferably 7.5 or more and 9 or less, and even more preferably 7.5 or more and 8.5 or less from the viewpoint of rapidly bringing the pH of the reaction solution to a neutralization point.

[0079] If the pH of the aqueous solution obtained by dissolving the alkali in water is within the prescribed range, it can be used directly as the alkaline aqueous solution (A). If the pH is outside the prescribed range, it can be used as the alkaline aqueous solution (A) after adjusting the pH to within the prescribed range with an acid. The acid used for pH adjustment can be selected from nitric acid, hydrochloric acid, hydrobromic acid, sulfuric acid, phosphoric acid, etc., and nitric acid is preferred from the viewpoint of efficiently washing the precipitate described later.

[0080] The alkaline aqueous solution (A) may also contain one or more solvents other than water. The one or more solvents other than water may be selected from organic solvents such as alcohols. Based on the volume of the alkaline aqueous solution (A), the total content of the one or more solvents other than water is usually less than 10 vol%, preferably less than 5 vol%. The lower limit is 0.

[0081] The metal elements (e.g., alkali metal elements such as Na and K) derived from the alkaline aqueous solution (A) are not the target metal elements to be contained in the composite oxide. Therefore, it is preferred to remove the metal elements (e.g., alkali metal elements such as Na and K) derived from the alkaline aqueous solution (A) from the precipitate. As described later, the removal can be performed by washing the precipitate.

[0082] The two or more metal ions contained in the acidic aqueous solution (B) are metal ions corresponding to the target metal elements to be contained in the composite oxide. There are no particular restrictions on the two or more metal ions contained in the acidic aqueous solution (B), as long as they can react with one or more selected from hydroxide ions, carbonate ions and bicarbonate ions in the alkaline aqueous solution (A), and optionally react with another one or more metal ions contained in the acidic aqueous solution (B) to form a water-insoluble hydroxide, a water-insoluble carbonate, a water-insoluble bicarbonate or a water-insoluble basic carbonate. For example, they can be selected from Cu, Zn, Zr, Mg, Al, etc. For example, a certain metal ion M1 2+ It can react with one or more of the hydroxide ions, carbonate ions and bicarbonate ions in the alkaline aqueous solution (A), and optionally with another metal ion M2 contained in the acidic aqueous solution (B). 2+ reaction, thereby forming M1(OH)2, M1CO3, [(M1 x M2 1-x )2(OH)2(CO3)](0<x≤1), etc.

[0083] When the composite oxide produced by the production method of the present invention is a composite oxide containing Cu, Zn and Zr, and particularly when it is the composite oxide of the present invention, the acidic aqueous solution (B) contains Cu ions, Zn ions and Zr ions.

[0084] When the composite oxide manufactured by the manufacturing method of the present invention contains, in addition to Cu, Zn and Zr, one or more other metal elements (such as Mg, Al, etc.), the acidic aqueous solution (B) may contain, in addition to Cu ions, Zn ions and Zr ions, one or more other metal ions (such as Mg ions, Al ions, etc.).

[0085] The acidic aqueous solution (B) can be prepared by dissolving two or more water-soluble metal salts in water and then adjusting the pH of the resulting aqueous solution as necessary.

[0086] The water-soluble metal salt used in the preparation of the acidic aqueous solution (B) is not particularly limited as long as it can be dissolved in water to generate the target metal ion. The water-soluble metal salt can be a salt whose aqueous solution is neutral, and from the viewpoint of the simplicity of preparation of the acidic aqueous solution (B), it is preferably a salt whose aqueous solution is acidic.

[0087] When the composite oxide manufactured by the manufacturing method of the present invention contains Cu, Zn, Zr and optionally one or more other metal elements (such as Mg, Al, etc.), the acidic aqueous solution (B) can be prepared by dissolving a water-soluble Cu salt, a water-soluble Zn salt, a water-soluble Zr salt and optionally one or more other water-soluble metal salts (such as a water-soluble Mg salt, a water-soluble Al salt, etc.) in water and then adjusting the pH of the resulting aqueous solution as needed.

[0088] Water-soluble Cu salts can be selected from, for example, copper nitrate, copper acetate, copper chloride, copper sulfate, copper carbonate, etc. The water-soluble Cu salt can be a salt whose aqueous solution is neutral, and from the viewpoint of the simplicity of preparation of the acidic aqueous solution (B), it is preferably a salt whose aqueous solution is acidic. The aqueous solution is an acidic water-soluble Cu salt, for example, can be selected from copper nitrate, copper sulfate, copper acetate, copper chloride, etc., and from the viewpoint of the simplicity of preparation of the acidic aqueous solution (B), it is preferably selected from copper nitrate and copper acetate. One water-soluble Cu salt can be used alone, or two or more water-soluble Cu salts can be used in combination.

[0089] The water-soluble Zn salt can be selected from zinc nitrate, zinc carbonate, zinc acetate, etc., for example. The water-soluble Zn salt can be a salt whose aqueous solution is neutral, and from the viewpoint of the simplicity of preparation of the acidic aqueous solution (B), it is preferably a salt whose aqueous solution is acidic. The water-soluble Zn salt whose aqueous solution is acidic can be selected from zinc nitrate, zinc acetate, etc., and from the viewpoint of the simplicity of preparation of the acidic aqueous solution (B), zinc nitrate is preferred. One water-soluble Zn salt can be used alone, or two or more water-soluble Zn salts can be used in combination.

[0090] The water-soluble Zr salt can be selected from, for example, zirconium oxynitrate, zirconium carbonate, zirconium chloride, etc. The water-soluble Zr salt can be a salt whose aqueous solution is neutral, but from the viewpoint of the simplicity of preparation of the acidic aqueous solution (B), it is preferably a salt whose aqueous solution is acidic. The water-soluble Zr salt whose aqueous solution is acidic can be selected from, for example, zirconium oxynitrate, zirconium chloride, etc., and from the viewpoint of the simplicity of preparation of the acidic aqueous solution (B), zirconium oxynitrate is preferred. One water-soluble Zr salt can be used alone, or two or more water-soluble Zr salts can be used in combination.

[0091] Other water-soluble metal salts can be selected from, for example, nitrates (e.g., magnesium nitrate, aluminum nitrate, etc.), carbonates (e.g., magnesium carbonate, aluminum carbonate, etc.), acetates (e.g., magnesium acetate, aluminum acetate, etc.), etc. Other water-soluble metal salts can also be salts whose aqueous solutions are neutral, but from the viewpoint of the ease of preparation of the acidic aqueous solution (B), salts whose aqueous solutions are acidic are preferred. Other water-soluble metal salts whose aqueous solutions are acidic can be selected from, for example, nitrates (e.g., magnesium nitrate, aluminum nitrate, etc.), etc. From the viewpoint of the ease of preparation of the acidic aqueous solution (B), nitrates (e.g., magnesium nitrate, aluminum nitrate, etc.) are preferred. One or more other water-soluble metal salts can be used alone, or two or more other water-soluble metal salts can be used simultaneously.

[0092] The pH of the acidic aqueous solution (B) is not particularly limited as long as a precipitate can be formed by mixing the alkaline aqueous solution (A) with the acidic aqueous solution (B), and is preferably 5 or less, more preferably 4 or less, further preferably 2 or less, further more preferably 1 or less, and particularly preferably 0.7 or less. The lower limit is not particularly limited. The pH of the acidic aqueous solution (B) can be, for example, 0.1 or more, 0.3 or more, 0.4 or more, or 0.5 or more. These lower limits can be combined with any of the above upper limits, respectively.

[0093] The aqueous solution obtained by dissolving two or more water-soluble metal salts in water can be used directly as an acidic aqueous solution (B) if the pH is within a specified range, and can be used as an acidic aqueous solution (B) after adjusting the pH to within a specified range using an acid if the pH is outside the specified range. The acid used for pH adjustment can be selected from nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid, etc., but nitric acid is preferred from the viewpoint of efficiently washing the precipitate described later.

[0094] The acidic aqueous solution (B) may contain one or more solvents other than water. The one or more solvents other than water can be selected from organic solvents such as alcohols. Based on the volume of the acidic aqueous solution (B), the total content of the one or more solvents other than water is usually 30 vol% or less, preferably 5 vol% or less. The lower limit is zero.

[0095] When the acidic aqueous solution (B) is added to the alkaline aqueous solution (A), each metal ion contained in the acidic aqueous solution (B) reacts with one or more of the hydroxide ions, carbonate ions and bicarbonate ions contained in the alkaline aqueous solution (A), and optionally reacts with another one or more metal ions contained in the acidic aqueous solution (B) to form a water-insoluble hydroxide, a water-insoluble carbonate, a water-insoluble bicarbonate or a water-insoluble basic carbonate, and precipitates. That is, a precipitate containing two or more metal elements is formed. The precipitate contains one or more particles selected from water-insoluble hydroxides, water-insoluble carbonates, water-insoluble bicarbonates and water-insoluble basic carbonates. Two or more particles selected from water-insoluble hydroxides, water-insoluble carbonates, water-insoluble bicarbonates and water-insoluble basic carbonates can also form composite particles. The two or more metal elements contained in the precipitate correspond to the two or more metal ions contained in the acidic aqueous solution (B).

[0096] When the acidic aqueous solution (B) contains Cu ions, Zn ions, Zr ions, and optionally one or more other metal ions, when the acidic aqueous solution (B) is added to the alkaline aqueous solution (A), each metal ion contained in the acidic aqueous solution (B) reacts with one or more selected from the group consisting of hydroxide ions, carbonate ions, and bicarbonate ions contained in the alkaline aqueous solution (A), and optionally reacts with another one or more metal ions contained in the acidic aqueous solution (B), thereby forming a poorly water-soluble hydroxide. (copper hydroxide, zinc hydroxide, zirconium hydroxide, hydroxides of one or more other metal elements), water-insoluble carbonates (copper carbonate, zinc carbonate, zirconium carbonate, carbonates of one or more other metal elements), water-insoluble bicarbonates (copper bicarbonate, zinc bicarbonate, zirconium bicarbonate, bicarbonates of one or more other metal elements) or water-insoluble basic carbonates (basic copper carbonate, basic zinc carbonate, basic zirconium carbonate, basic carbonates of one or more other metal elements), and precipitate. That is, a precipitate containing Cu, Zn, Zr and optionally one or more other metal elements is formed. The precipitate contains one or more particles selected from the water-insoluble hydroxides, water-insoluble carbonates, water-insoluble bicarbonates and water-insoluble basic carbonates of the above-mentioned metals. Two or more particles selected from the water-insoluble hydroxides, water-insoluble carbonates, water-insoluble bicarbonates and water-insoluble basic carbonates can also form composite particles.

[0097] From the viewpoint of making the structure and composition of the generated reaction intermediate uniform, the pH of the alkaline aqueous solution (A) (i.e., the mixed solution of the alkaline aqueous solution (A) and the acidic aqueous solution (B)) after adding the acidic aqueous solution (B) is preferably 5 or more and 9 or less, more preferably 7 or more and 8 or less. The pH of the alkaline aqueous solution (A) after adding the acidic aqueous solution (B) refers to the pH of the alkaline aqueous solution (A) just after the addition of the acidic aqueous solution (B). After the addition of the acidic aqueous solution (B), the pH of the reaction solution sometimes increases over time. When the precipitate is matured, the pH of the reaction solution after the precipitate is matured sometimes increases by 1 to 2 compared to the pH of the reaction solution before the precipitate is matured.

[0098] From the viewpoint of making the pH of the entire reaction solution uniform and increasing the specific surface area of ​​the produced composite oxide, when adding the acidic aqueous solution (B) to the alkaline aqueous solution (A), it is preferred to stir the alkaline aqueous solution (A) while dripping the acidic aqueous solution (B) into the alkaline aqueous solution (A).

[0099] From the viewpoint of promoting the formation of reaction intermediates, the temperature of the alkaline aqueous solution (A) when adding the acidic aqueous solution (B) is preferably 10°C to 90°C, more preferably 25°C to 80°C, and even more preferably 30°C to 70°C.

[0100] From the viewpoint of achieving uniform formation of reaction intermediates, the temperature of the acidic aqueous solution (B) when added to the alkaline aqueous solution (A) is preferably 10°C to 90°C, more preferably 25°C to 80°C, and even more preferably 30°C to 70°C.

[0101] From the viewpoint of achieving uniform formation of the reaction intermediate, it is preferred to ripen the precipitate while stirring the alkaline aqueous solution (A) after adding the acidic aqueous solution (B). The ripening time is preferably from 1 hour to 24 hours, more preferably from 1 hour to 20 hours, and further preferably from 1 hour to 12 hours. The ripening temperature is preferably from 10°C to 90°C, more preferably from 25°C to 80°C, and further preferably from 30°C to 70°C.

[0102] The amount of the alkaline aqueous solution (A) prepared, the concentration of metal ions contained in the acidic aqueous solution (B), the amount of the acidic aqueous solution (B) added to the alkaline aqueous solution (A), etc. can be appropriately adjusted according to the composition of the composite oxide produced by the production method of the present invention.

[0103] The precipitate obtained in step (a) is preferably washed with a cleaning solution before being supplied to step (b). As the cleaning solution, water can be used. The precipitate can be washed by contacting the precipitate with a cleaning solution (for example, by mixing the precipitate with the cleaning solution). After the precipitate is in contact with the cleaning solution, solid-liquid separation is performed, thereby obtaining the washed precipitate in the form of a filter cake. The solid-liquid separation method can be selected from, for example, filtration, centrifugation, decantation, etc. The washing of the precipitate is preferably carried out until the pH of the filtrate or supernatant obtained by solid-liquid separation after the precipitate is in contact with the cleaning solution reaches 8.5 or less (especially 7.5 or less). In addition, the washing of the precipitate is preferably carried out until the amount of metal elements (for example, alkali metal elements such as Na and K) derived from the alkaline aqueous solution (A) contained in the filtrate or supernatant obtained by solid-liquid separation after the precipitate is in contact with the cleaning solution reaches 15 ppm or less (especially 10 ppm or less).

[0104] For the precipitate obtained in step (a), it is preferably made into a filter cake before being supplied to step (b), and the filter cake is dried. In the case of washing the precipitate, it is preferably made into a filter cake after washing, and the filter cake is dried. Drying can be carried out according to conventional methods. There are no particular restrictions on the drying temperature and drying time as long as the conditions are such that the filter cake is fully dried. For example, the drying temperature is usually above 70°C and below 200°C, preferably above 80°C and below 150°C, and the drying time is usually above 5 hours and below 30 hours, preferably above 10 hours and below 25 hours. By measuring the moisture content, it can be determined that the filter cake has been fully dried. The moisture content after drying is preferably above 0% by mass and below 5% by mass.

[0105] The dried cake may be crushed as needed before being subjected to step (b). The crushing may be carried out according to conventional methods. The crushing may be carried out, for example, by a mortar, hammer mill, ball mill, bead mill, jet mill, roller mill, etc., in a dry or wet manner.

[0106] <Step (b)>

[0107] The step (b) is a step of calcining the precipitate formed in the step (a) to produce a composite oxide containing two or more metal elements.

[0108] The calcination of the precipitate can be carried out according to a conventional method. The calcination is usually carried out in an air atmosphere. The calcination temperature is usually 100°C to 700°C, preferably 200°C to 600°C, more preferably 300°C to 500°C. The calcination time is usually 1 hour to 10 hours, preferably 1 hour to 8 hours, more preferably 2 hours to 6 hours.

[0109] The calcined product of the precipitate can be pulverized as needed. The pulverization can be performed according to a conventional method. For example, the pulverization can be performed in a dry or wet manner using a mortar, a hammer mill, a ball mill, a bead mill, a jet mill, a roller mill, or the like.

[0110] By calcining the precipitate, a composite oxide containing two or more metal elements can be obtained. The two or more metal elements contained in the composite oxide correspond to the two or more metal ions contained in the acidic aqueous solution (B).

[0111] When the acidic aqueous solution (B) contains Cu ions, Zn ions, Zr ions and optionally one or more other metal ions (such as Mg ions, Al ions, etc.), a composite oxide containing Cu, Zn, Zr and optionally one or more other metal elements (such as Mg, Al, etc.) can be obtained, especially the composite oxide of the present invention can be obtained.

[0112] According to the manufacturing method of the present invention, a composite oxide having one or more of the above-mentioned specific surface area, Cu dispersion and CuO crystallite diameter can be manufactured. The composite oxide manufactured using the manufacturing method of the present invention can exhibit excellent carbon dioxide methanolization catalytic performance (for example, CO2 conversion rate, methanol yield, etc.).

[0113] Example

[0114] [Example 1]

[0115] (1) Precipitation Formation Process

[0116] In one container, 504.1 g of sodium bicarbonate was dissolved in 6 L of pure water to prepare a 1 mol / L alkaline aqueous solution (liquid temperature 40°C, pH 8.3). In another container, 223.1 g (0.92 mol) of copper nitrate trihydrate, 103.0 g (0.35 mol) of zinc nitrate hexahydrate and 61.7 g (0.23 mol) of zirconium oxynitrate dihydrate were dissolved in 1.5 L of pure water to prepare an acidic aqueous solution (liquid temperature 40°C, pH 0.6). The alkaline aqueous solution was heated to 60°C, and then the acidic aqueous solution was added dropwise to the alkaline aqueous solution at a constant speed using a tube pump over 40 minutes while stirring the alkaline aqueous solution to form a precipitate, thereby obtaining a suspension (liquid temperature 60°C, pH 7.1).

[0117] (2) Cleaning process

[0118] The obtained suspension was stirred at 60°C for 2 hours while the precipitate was aged. The aged suspension was air-cooled and the supernatant was removed. About 10 L of pure water was added to the remaining suspension in the container, and after standing for 1 hour, the supernatant was removed again. This washing operation was repeated until the pH of the supernatant reached 7 or less and the Na ion concentration in the supernatant reached below the detection limit.

[0119] (3) Composite oxide production process

[0120] The suspension subjected to the washing step was suction filtered, and the obtained filter cake was dried overnight in a drying chamber at 100° C. The dried block was crushed in an agate mortar, and the crushed powder was calcined at 400° C. for 4 hours in an air atmosphere to obtain a composite oxide containing Cu, Zn, and Zr.

[0121] [Example 2]

[0122] The same operation as in Example 1 was carried out except that the precipitate forming step was carried out as follows, thereby obtaining a composite oxide containing Cu, Zn, Zr, and Mg.

[0123] The precipitate formation process in Example 2 is as follows.

[0124] In one container, 336.0 g of sodium bicarbonate was dissolved in 4 L of pure water to prepare a 1 mol / L alkaline aqueous solution (liquid temperature 25°C, pH 8.0). In another container, 144.2 g (0.60 mol) of copper nitrate trihydrate, 66.6 g (0.22 mol) of zinc nitrate hexahydrate, 39.9 g (0.15 mol) of zirconium oxynitrate dihydrate and 7.7 g (0.03 mol) of magnesium nitrate were dissolved in 1 L of pure water to prepare an acidic aqueous solution (liquid temperature 40°C, pH 0.6). The alkaline aqueous solution was heated to 60°C, and then the acidic aqueous solution was added dropwise to the alkaline aqueous solution at a constant speed using a tube pump over 25 minutes while stirring the alkaline aqueous solution to form a precipitate, thereby obtaining a suspension (liquid temperature 60°C, pH 7.2).

[0125] [Example 3]

[0126] The same operation as in Example 1 was carried out except that the precipitate forming step was carried out as follows, thereby obtaining a composite oxide containing Cu, Zn, Zr, and Al.

[0127] The precipitate formation process in Example 3 is as follows.

[0128] In one container, 336.0 g of sodium bicarbonate was dissolved in 4 L of pure water to prepare a 1 mol / L alkaline aqueous solution (liquid temperature 25°C, pH 8.0). In another container, 195.1 g (0.81 mol) of copper nitrate trihydrate, 103.0 g (0.35 mol) of zinc nitrate hexahydrate, 46.3 g (0.17 mol) of zirconium oxynitrate dihydrate, and 64.9 g (0.17 mol) of aluminum nitrate nonahydrate were dissolved in 1.5 L of pure water to prepare an acidic aqueous solution (liquid temperature 25°C, pH 0.4). The alkaline aqueous solution was heated to 60°C, and then the acidic aqueous solution was added dropwise to the alkaline aqueous solution at a constant speed over 25 minutes using a tube pump while stirring the alkaline aqueous solution to form a precipitate, thereby obtaining a suspension (liquid temperature 60°C, pH 7.2).

[0129] [Comparative Example 1]

[0130] A composite oxide containing Cu, Zn, and Zr was obtained by performing the same operation as in Example 1 except that the precipitate forming step was performed as follows.

[0131] The precipitate forming process in Comparative Example 1 is as follows.

[0132] In one container, 208.1 g (0.86 mol) of copper nitrate trihydrate, 96.1 g (0.32 mol) of zinc nitrate hexahydrate and 57.6 g (0.22 mol) of zirconium oxynitrate dihydrate are dissolved in 1.4 L of pure water to prepare an acidic aqueous solution (liquid temperature 25°C, pH 0.4). In another container, a 1.2 mol / L sodium carbonate aqueous solution is prepared. The acidic aqueous solution is heated to 60°C, and then the sodium carbonate aqueous solution is quickly added to the acidic aqueous solution while the acidic aqueous solution is vigorously stirred to form a precipitate and prepare a suspension. The sodium carbonate aqueous solution is continuously added until the pH of the suspension stabilizes at about 8.0.

[0133] [Comparative Example 2]

[0134] The same operation as in Example 1 was carried out except that the precipitate forming step was carried out as follows, thereby obtaining a composite oxide containing Cu, Zn, Zr, and Mg.

[0135] The precipitate forming step in Comparative Example 2 is as follows.

[0136] In one container, 201.9 g (0.84 mol) of copper nitrate trihydrate, 93.2 g (0.31 mol) of zinc nitrate hexahydrate, 55.8 g (0.21 mol) of zirconium nitrate dihydrate and 10.7 g (0.04 mol) of magnesium nitrate hexahydrate were dissolved in 1.4 L of pure water to prepare an acidic aqueous solution (liquid temperature 25°C, pH 0.4). In another container, a 1.2 mol / L sodium carbonate aqueous solution was prepared. The acidic aqueous solution was heated to 60°C, and then the sodium carbonate aqueous solution was rapidly added to the acidic aqueous solution while the acidic aqueous solution was vigorously stirred to prepare a suspension. The sodium carbonate aqueous solution was continuously added until the pH of the suspension stabilized at about 8.0.

[0137] [Comparative Example 3]

[0138] The same operation as in Example 1 was carried out except that the precipitate forming step was carried out as follows, thereby obtaining a composite oxide containing Cu, Zn, Zr, and Al.

[0139] The precipitate forming process in Comparative Example 3 is as follows.

[0140] In one container, 182.1 g (0.75 mol) of copper nitrate trihydrate, 96.1 g (0.32 mol) of zinc nitrate hexahydrate, 43.2 g (0.16 mol) of zirconium nitrate dihydrate, and 60.6 g (0.16 mol) of aluminum nitrate nonahydrate were dissolved in 1.4 L of pure water to prepare an acidic aqueous solution (liquid temperature 30°C, pH 0.4). In another container, a 1.2 mol / L sodium carbonate aqueous solution was prepared. The acidic aqueous solution was heated to 60°C, and then the sodium carbonate aqueous solution was rapidly added to the acidic aqueous solution while the acidic aqueous solution was vigorously stirred. The sodium carbonate aqueous solution was continuously added until the pH of the suspension stabilized at about 8.0.

[0141] [Comparative Example 4]

[0142] A composite oxide containing Cu, Zn, and Zr was obtained by performing the same operation as in Example 1 except that the precipitate forming step was performed as follows.

[0143] The precipitate forming step in Comparative Example 4 was as follows.

[0144] In one container, 268.0 g of sodium carbonate was dissolved in 2.1 L of pure water to prepare a 1.2 mol / L sodium carbonate aqueous solution (liquid temperature 25°C, pH 11.7). In another container, 193.3 g (0.80 mol) of copper nitrate trihydrate, 89.3 g (0.30 mol) of zinc nitrate hexahydrate and 75.0 g (0.28 mol) of zirconium oxynitrate dihydrate were dissolved in 1.4 L of pure water to prepare an acidic aqueous solution (liquid temperature 30°C, pH 0.5). The sodium carbonate aqueous solution was heated to 60°C, and then the acidic aqueous solution was added dropwise to the sodium carbonate aqueous solution at a constant speed using a tube pump over 55 minutes while stirring the sodium carbonate aqueous solution to form a precipitate and obtain a suspension (liquid temperature 60°C, pH 7.5).

[0145] [Test Example 1]

[0146] The content of each metal element, specific surface area, Cu dispersion and CuO crystallite diameter were measured for the composite oxides obtained in Examples 1 to 3 and Comparative Examples 1 to 4. The results are shown in Table 1. The content of each metal element, specific surface area, Cu dispersion and CuO crystallite diameter were measured as follows.

[0147] <Content of each metal element>

[0148] The content (mass) of each metal element in the composite oxide is measured by inductively coupled plasma emission spectrometry (ICP-AES or ICP-OES). Based on the measured value, the content (molar amount) of each metal element is calculated. The calculation results are shown in Table 1. In Table 1, there is a case where the total content (molar amount) of each metal element contained in the composite oxide does not reach 100%, because the decimal point of the content of each element is rounded off.

[0149] <Specific surface area>

[0150] In order to remove the moisture contained in the composite oxide, the composite oxide was heat treated at 120°C for 10 minutes in an atmospheric atmosphere. The specific surface area of ​​the composite oxide after heat treatment was measured. The specific surface area was measured by the BET single point method using a commercially available BET specific surface area measuring device (BELSORP MR6 manufactured by Microtrack Bell Co., Ltd.). The BET single point method was performed in accordance with "(3.5) Single Point Method" in "6.2 Flow Method" of JIS R1626:1996 "Method for Determining the Specific Surface Area of ​​Fine Ceramic Powders by Gas Adsorption BET Method". As a gas, a nitrogen-helium mixed gas containing 30 volume % of nitrogen as an adsorbed gas and 70 volume % of helium as a carrier gas was used, and single point measurement was performed in the range of equilibrium relative pressure of 0.05 to 0.35.

[0151] <Cu dispersion>

[0152] For the determination of Cu dispersion, a commercially available metal dispersion measuring device (BELMETAL3 manufactured by Microtrac bel Co., Ltd.) was used to perform the determination using the N2O pulse adsorption method. The N2O pulse adsorption method refers to a method in which N2O gas is introduced into the sample in a pulsed state until saturation is reached, and the Cu dispersion on the sample is calculated based on the total amount of gas consumption. The N2O pulse adsorption measurement results are analyzed in the automatic analysis mode of the waveform analysis software "ChemMaster" attached to the device. At this time, the stoichiometric ratio representing the number of N2O molecules adsorbed by one Cu metal atom is set to 2, and the dispersion is calculated. Perform the analysis in accordance with the "ChemMaster Waveform Analysis Software User Manual (Ver.1.3) Microtrac bel Co., Ltd."

[0153] Here, the Cu dispersion refers to the ratio of the number B of Cu atoms exposed on the surface of the composite oxide to the total number A of Cu atoms in the composite oxide, and is calculated by Cu dispersion (%) = (B / A) × 100. The number B of Cu atoms exposed on the surface of the composite oxide is calculated based on the premise that the Cu atoms exposed on the surface of the composite oxide are adsorbed with N2O at a ratio of 1:2, based on the amount of N2O adsorbed measured by the N2O pulse method. The calculation method is as follows.

[0154] (Calculation method)

[0155] The amount of N2O gas adsorbed at the measured temperature according to the sample weight W (g) t , and the amount of adsorbed gas V per 1 g of the composite oxide at 0°C was calculated based on the following formula (1).

[0156] V(mL / g)=(V t / W)×{273 / (273+t)} ··· (1)

[0157] Here, when the Cu content of the sample is represented by C (mass %) and the atomic weight of Cu is represented by M, the number of moles R of Cu per 1 g of the sample is calculated based on the following formula (2).

[0158] R(mol / g)=(C / 100)×(1 / M) ··· (2)

[0159] The number of moles K of the amount of adsorbed gas per 1 g of the sample was calculated based on the following formula (3).

[0160] K(mol / g)=V / (22.4×10 -3 ×10 6 )···(3)

[0161] Thus, the Cu dispersion D is calculated based on the following formula (4) using the stoichiometric ratio S indicating the number of N 2 O molecules adsorbed by one Cu metal atom.

[0162] D(%)=(K / S)×(1 / R)×100··· (4)

[0163] <CuO crystallite diameter>

[0164] The composite oxide was analyzed by X-ray diffraction (XRD) using a commercially available powder X-ray diffractometer (SmartLab manufactured by Rigaku Co., Ltd.) to obtain an X-ray diffraction pattern of the composite oxide. XRD was performed under the conditions of X-ray source: CuKα, operating axis: 2θ / θ, measurement method: continuous, counting unit: cps, starting angle: 5°, ending angle: 80°, sampling width: 0.02°, scanning speed: 10° / min, voltage: 40kV, current: 150mA. In the X-ray diffraction pattern of the composite oxide, the peak at 2θ=38.8°±0.5° among the diffraction peaks originating from CuO was determined, and the Scherrer formula was applied to the determined peak to calculate the crystallite diameter. The crystallite diameter obtained based on the peak at 2θ=38.8°±0.5° is taken as the CuO crystallite diameter. It should be noted that the Scherrer formula is as follows.

[0165] D=K×λ / Bcosθ

[0166] [Where D is the crystallite size (nm), K is the Scherrer constant, λ is the wavelength of the X-ray (nm), B is the broadening of the diffraction line width (rad), and θ is the Bragg angle (rad).]

[0167] [Test Example 2]

[0168] The carbon dioxide methanolization catalytic performance (CO2 conversion rate and methanol yield) was measured for the composite oxides obtained in Examples 1 to 3 and Comparative Examples 1 to 4. The measurement method is as follows.

[0169] In order to reduce the Cu oxide (i.e., CuO) contained in the composite oxide to form Cu with a lower valence than before reduction, the composite oxide was heat treated at 100°C for 1 hour in a 100% H2 atmosphere, and then heat treated at 300°C for 1 hour in a 100% H2 atmosphere. The catalytic activity of the composite oxide after heat treatment was evaluated using a reaction tube made of SUS316 and having an inner diameter of 10.22 mm. At this time, the sample volume was set to 2 cm 3, the sample size was set to 500μm to 1mm mesh size, the evaluation gas flow rate was set to Total gas flow rate 100L / hr (CO2: 25L / hr, H2: 75L / hr, CO2:H2=1:3), the space velocity (SV) was set to 50,000 (1 / h), the temperature was set to 250°C, and the pressure was set to 15MPa. The online gas at the outlet of the reaction tube was quantified using GC-FID (Gas Chromatography-Flame Ionization Detector) to determine the CO2 conversion rate and methanol yield. The CO2 conversion rate was determined based on the amount of CO2 reduction. The methanol yield was determined based on the amount of methanol obtained by quantification. The results are shown in Table 1.

[0170] [Table 1]

[0171]

[0172] As shown in Table 1, the composite oxides obtained in Examples 1 to 3 have (physical property 1) a specific surface area of ​​50 m 2 / g or more and (physical property 2) Cu dispersion of 6.5% or more, while the composite oxides obtained in Comparative Examples 1 to 4 did not have at least one of physical properties 1 and 2.

[0173] As shown in Table 1, the composite oxides obtained in Examples 1 to 3 were superior to the composite oxides obtained in Comparative Examples 1 to 4 in terms of carbon dioxide methanolation catalytic performance (CO 2 conversion rate and methanol yield).

Claims

1. A composite oxide comprising Cu, Zn and Zr, having a specific surface area of ​​50 m 2 / g or more, and the Cu dispersion is 6.5% or more.

2. The composite oxide according to claim 1, wherein Based on the total content of all metal elements in the composite oxide, the contents of Cu, Zn and Zr in the composite oxide are respectively 40 mol% to 90 mol%, 5 mol% to 40 mol%, and 1 mol% to 15 mol%. 3 . The composite oxide according to claim 1 , further comprising one or two metal elements selected from Mg and Al.

4. The composite oxide according to claim 1 or 2, wherein The CuO crystallite diameter is 2.0 nm or more and 25.0 nm or less. 5 . A catalyst for methanol production, comprising the composite oxide according to claim 1 or 2 .

6. A method for producing a composite oxide, comprising the following steps: Step (a), adding an acidic aqueous solution containing two or more metal ions to an alkaline aqueous solution having a pH of 7.5 or more and 11 or less to form a precipitate containing two or more metal elements; and In step (b), the precipitate is calcined to produce a composite oxide containing the two or more metal elements.

7. The manufacturing method according to claim 6, wherein: In the step (a), the pH of the alkaline aqueous solution after the addition of the acidic aqueous solution is 5 or more and 9 or less.

8. The manufacturing method according to claim 6 or 7, wherein: The acidic aqueous solution used in step (a) contains Cu ions, Zn ions, and Zr ions, and the composite oxide produced in step (b) contains Cu, Zn, and Zr.

9. The manufacturing method according to claim 8, wherein: The composite oxide produced in step (b) further contains one or two metal elements selected from Mg and Al.

10. The manufacturing method according to claim 8, wherein: The composite oxide produced in step (b) is the composite oxide according to claim 1 or 2.

11. A method for producing methanol, comprising the step of contacting CO2 gas and H2 gas under the conditions of 100°C to 400°C and 0.1 MPa to 30 MPa in the presence of the composite oxide according to claim 1 or 2 which has been subjected to a reduction treatment.

Citation Information

Patent Citations

  • Methanol synthesis catalyst and manufacture thereof

    JP1995039755A